2013
DOI: 10.1016/j.actamat.2013.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of metastable tetragonal disordered phase upon phase transitions in the equiatomic nanostructured FePd alloy

Abstract: Specific features of the phase transformation A1 ! L1 0 (space groups Fm3m and P4/mmm, respectively) in single crystals of the equiatomic alloy FePd subjected to annealings both in the absence and in the presence of external uniaxial load, as well as in polycrystalline samples that had undergone severe plastic deformation via high-pressure torsion and subsequent annealing, have been studied. An investigation of the single crystals in a nanostructured state formed at different stages of ordering annealing was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
(108 reference statements)
5
20
0
Order By: Relevance
“…The diffuse scattering took the form of a low-intensity, semi-regular waveform concentrated at low dspacings, consistent with that produced by type-1 Krivoglaz defects [45] such as coherent precipitates, and was most clearly observable in the deformed post-anneal Fe 62 Ni sample. This diffuse scattering signal is hypothesized to be associated with the formation of a pretransition state, in accordance with analogous observations of Vlasova et al of electron diffraction patterns obtained from equiatomic FePd single crystals subjected to annealing and quenching processes [46]. It is preliminarily concluded that the diffuse neutron scattering signal observed from the processed FeNi samples is consistent with local correlations that are related to a very short-range chemical order phenomena.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The diffuse scattering took the form of a low-intensity, semi-regular waveform concentrated at low dspacings, consistent with that produced by type-1 Krivoglaz defects [45] such as coherent precipitates, and was most clearly observable in the deformed post-anneal Fe 62 Ni sample. This diffuse scattering signal is hypothesized to be associated with the formation of a pretransition state, in accordance with analogous observations of Vlasova et al of electron diffraction patterns obtained from equiatomic FePd single crystals subjected to annealing and quenching processes [46]. It is preliminarily concluded that the diffuse neutron scattering signal observed from the processed FeNi samples is consistent with local correlations that are related to a very short-range chemical order phenomena.…”
Section: Resultssupporting
confidence: 75%
“…Vlasova et al [46] has recently reported that the A6 structure exists as a symmetry-permitted transitional tetragonal phase in the FePd system, bridging the disordered cubic A1 phase and the chemically ordered tetragonal L1 0 FePd phase. She predicted that this A6 structure likely exists in other L1 0 -forming alloys as well.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, inspired by previous work performed on the FePd alloy system, a custom-built annealing furnace is employed to study the effects of extrinsic factors (magnetic field, mechanical stress) on phase selection in L1 0 -phase forming compounds [27], [29].…”
Section: Objective (Ii): Analyzing the Formation Of Magnetocrystallinmentioning
confidence: 99%
“…For these reasons, L1 0 FeNi has only been found naturally in stony, stony-iron, or iron meteorites that have cooled extremely slowly over billions of years [31]- [34]. Due to these sluggish transformation kinetics it has been decidedly difficult to study details of the transformation process and the extrinsic factors that impact this high magnetocrystalline anisotropy [27]- [30], [35]. Furthermore, identification of the L1 0 phase can be a challenge, particularly for L1 0 FeNi, due to the similarity of the X-ray scattering cross sections of Fe and Ni as well as the very small tetragonal distortion (c/a ~ 1.0036) that accompanies the transformation to the L1 0 phase.…”
Section: Objective (Ii): Analyzing the Formation Of Magnetocrystallinmentioning
confidence: 99%
See 1 more Smart Citation